English Teaching in Inclusive Classrooms for Students with Intellectual Disability - Dewa Ayu Gede Rias Wicha Nofitri; I. G. A. Lokita Purnamika Utami; Luh Gd Rahayu Budiarta (English Education Department STKIP Agama Hindu Singaraja, 2026)
This study investigated the implementation of English teaching in an inclusive classroom consisting of regular students and a student with intellectual disability at SMP PGRI 6 Denpasar. The study aimed to identify the teaching procedures implemented by the teacher, the challenges faced during the teaching and learning process, and the strategies used to overcome those challenges. This study employed a descriptive qualitative case study design. The participant was an English teacher who taught ninth-grade students in an inclusive classroom. Data were collected through classroom observations and interviews. The findings revealed that the English teaching procedures in the inclusive classroom generally followed three stages: pre-activity, whilst-activity, and post-activity. Although the teacher applied the same learning process to all students, additional attention was provided to the student with intellectual disability, particularly during reading, pronunciation practice, and group discussion activities. The study also found several challenges, including students’ difficulty in maintaining focus and limitations in language mastery. To address these challenges, the teacher implemented several strategies, such as group work activities, peer support, individual assistance, and assigning tasks similar to those given to regular students. The study concludes that inclusive English teaching can be implemented effectively when teachers provide equal learning opportunities while still adapting instruction to students’ individual needs.